METHODS OF DEVELOPING STUDENTS' DESIGN ABILITY - Boburmirzo Kukiyev (Western European Studies, 2024)
Developing students' design skills using graphic programs and 3D printers and other programs. In addition, theoretical information on the development of design skills is presented.
Keywords: Technology; creativity; design